Strategi Unit Pengumpul Zakat Jatisono Demak dalam Penghimpunan Zakat Pertanian - Aan Zainul Anwar; Muhammad Ismail (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
This study aims to determine the potential of agricultural zakat and agricultural zakat collection strategies at UPZ Baznas Jatisono, Demak Regency, Central Java. The type of research is field research using descriptive qualitative methods. The data collection technique was through observing the implementation of agricultural zakat on farmers in Jatisono village and in-depth interviews with informants managing BAZNAS Demak, UPZ Jatisono managers, and farmers who as muzakki. Documentation from BPS (Indonesian Statistic Agency) data for Demak Regency, area field data, muzakki data, financial reports, and zakat reports. The results showed that the total agricultural produce that UPZ Jatisono was able to collect every year always reached the potential target, this was because the determination of potential was carried out during the planting season and was based on the area of ​​rice fields with the collection strategy, namely providing zakat services by distributing Karkat (Zakat Card). Furthermore, UPZ Jatisono formed a coordinator of amil zakat in prayer rooms and mosques. During the harvest season, UPZ opens the UPZ building to pay zakat according to the scheduled time. During the post-harvest season, UPZ reports the results of zakat collected through the mosque which is broadcast before the Friday prayer.